Microbiome engineering optimized by Antarctic microbiota to support a plant host under water deficit - Rodríguez, Rodrigo; Barra, Patricio J.; Larama, Giovanni; Carrion, Víctor J.; de la Luz Mora, María; Hale, Lauren; Durán, Paola (Frontiers in Plant Science, 2023)
Climate change challenges modern agriculture to develop alternative and eco-friendly solutions to alleviate abiotic and/or biotic stresses. The use of soil microbiomes from extreme environments opens new avenues to discover novel microorganisms and microbial functions to protect plants. In this study we confirm the ability of a bioinoculant, generated by natural engineering, to promote host development under water stress. Microbiome engineering was mediated through three factors i) Antarctic soil donation, ii) water deficit and iii) multigenerational tomato host selection. We revealed that tomato plants growing in soils supplemented with Antarctic microbiota were tolerant to water deficit stress after 10 generations. A clear increase in tomato seedling tolerance against water deficit stress was observed in all soils over generations of Host Mediated Microbiome Engineering, being Fildes mixture the most representatives, which was evidenced by an increased survival time, plant stress index, biomass accumulation, and decreased leaf proline content. Microbial community analysis using 16s rRNA gene amplicon sequencing data suggested a microbiome restructuring that could be associated with increased tolerance of water deficit. Additionally, the results showed a significant increase in the relative abundance of Candidatus Nitrosocosmicus and Bacillus spp. which could be key taxa associated with the observed tolerance improvement. We proposed that in situ microbiota engineering through the evolution of three factors (long-standing extreme climate adaption and host and stress selection) could represent a promising strategy for novel generation of microbial inoculants.